Perlindungan Hukum Pemilik Sertifikat Hak Milik Satuan Rumah Susun atas Kehancuran Unit Apartemen - Rizki Namira; Virnindya Putri; Doddy Putra (CV Rewang Rencang, 2025)
The attractiveness of apartment buildings for many parties, especially in urban areas with limited land, is undeniable. However, within these buildings, the possibility of issues such as damaged or deteriorating structures remains, which requires accountability from the owners of individual apartment units. This study explores the legal responsibility of building developers toward the owners of SHM Sarusun for building damage, as well as the legal actions available to SHM Sarusun owners. The research findings indicate that developers are obligated, in accordance with the Apartment Law, to maintain the building's quality and provide guarantees to owners. In case of damage, SHM owners are entitled to claim compensation through civil lawsuits, consumer mechanisms, or alternative dispute resolution.